Formulasi Strategi Bisnis Model Kemitraan Mobile Selling pada UMKM: Pendekatan Matriks Internal-External (Studi: PT Tumbuh Bersama Soyanara) - Futra, Fharel Az Zihra Adhie; Afkar, Muhammad Riyadh; Harir, Jihan Azizah; Fadhilah, Nida Nur; Hasanah, Sarah Nahdiyatul; Husyairi, Khoirul Aziz (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study analyzes the development strategy of PT Tumbuh Bersama Soyanara, a fresh soy milk distributor operating through a mobile partnership model, using SWOT analysis integrated with IFE-EFE-IE matrices. A qualitative single case study approach was employed, involving in-depth interviews with the CEO/Founder, three-day participatory observation of five partners’ operations, and internal document analysis. The findings reveal that the company is positioned in Cell V (Hold and Maintain) of the IE Matrix (IFE score 2.34; EFE score 2.43), indicating that internal weaknesses—manual recording systems, weak FIFO enforcement causing 8–12% waste, managerial response delays, and service quality inconsistencies—have not been adequately offset by institutional strengths. In response, a three-phase strategic framework is proposed: (1) operational excellence through digital transformation (months 0–6), (2) intensive market penetration via B2B partnerships and product portfolio optimization (months 6–12), and (3) customer intelligence leveraging habit-based personalization and payday-optimized bundling (months 12–24). Digital infrastructure functions as a governance mechanism that reduces information asymmetry and agency costs, thereby transforming operational weaknesses into sustainable competitive advantages.